Cuidados al adulto mayor en la prevención de caídas.Octubre 2019 – Febrero 2020 - Yambay Bonifaz, Rosa Elizabeth (2020)
In the Provincial, General Teaching Hospital Riobamba, Internal Medicine area, this research is carried out with the aim of determining the attention at the elderly in falling down circumstances prevention. October 2019 - February 2020; it is based on a descriptive study. The study population was made up of 12 graduates and 12 nursing assistants who provide their service in such area, in which two instruments were applied, the survey that allowed us to describe the socio-demographic characteristics and asses their knowledge, another instrument used is the observation guide based on the Patient Safety protocol, which shows the care that nursing personnel apply to this group of patients. Obtaining as results that the female sex prevails in the nursing staff in ages from 31 to 50 years old with about 2 to 4 years of experience, in the same way it was shown that the nursing staff check the patient in a falling risk and identifies this risk factors, to perform prevention activities in falls. With this research it was possible to identified that 59% of nursing graduates know the name by which this risk is measured "Morse Scale", this let us to think that we are able to carry out all activities to prevent falls. The staff of Internal Medicine service has for sure a Patient Safety protocol, which includes the "Prevention of Falls" and the form to report adverse events in the patient. In the other hand, nursing professionals do not carry out care plans based on the NANDA, NOC and NIC taxonomies, which indicates that the care provided requires a greater updating.